Percutaneous Ultrasound Guided Celiac Plexus Approach: Results in a Pig Cadaveric Model - Francesco Aprea; Yolanda Millán; Anna Tomás; Rocío Navarrete Calvo; María del Mar Granados (Animals)
Celiac plexus (CP) block (CPB) and neurolysis (CPN) are interventional techniques employed in human analgesia to control visceral pain originating from the upper abdomen. Visceral pain is common in animals and its treatment is challenging. A percutaneous ultrasound (US)-guided approach to the CP has been reported in people but not in veterinary species. The objective of this study is to describe a US-guided percutaneous approach to the CP in a porcine cadaveric model. Cadavers were positioned in right lateral recumbency. The vertebral body of the last thoracic vertebra (T15) was identified (in transverse view) with a left cranial abdominal US scan. Under US guidance, an 18 G Tuohy needle was inserted parallel and ventral to the transverse process of T15. The transducer was gently slid and tilted to have an in-plane view while introducing the needle through the epaxial muscle layer. Once the T15 body was contacted, the needle was advanced towards the ventral surface of the vertebra, and if loss of resistance was present, 2 mL of dye (China Ink) was injected. A laparotomy was performed, and the dyed tissue dissected for histological preparation from 14 cadavers. In all samples submitted for histological study, tissue belonging to the CP was found. The percutaneous ultrasound-guided approach to the CP was effective in localizing the CP in all subjects. Future studies are warranted to identify the clinical utility of this technique in veterinary species.